Corrosion Behavior and Passive Film Characterization of Fe50Mn30Co10Cr10 Dual-Phase High-Entropy Alloy in Sulfuric Acid Solution. Issue 8 (6th May 2020) - Lu, Yi-Sheng; Lu, Che-Wei; Lin, Yi-Ting; Yen, Hung-Wei; Lee, Yueh-Lien
Abstract : This study investigated the corrosion properties of a Fe50 Mn30 Co10 Cr10 dual-phase high-entropy alloy (DP-HEA) in 0.1 M H2 SO4 aqueous solution. The observed corrosion properties of the DP-HEA were compared with those of an equiatomic CoCrFeMnNi high-entropy alloy (HEA). Moreover, a passive film formed on the surface of the DP-HEA in an acidic environment was directly imaged and characterized for the first time through high-resolution transmission electron microscopy (HR-TEM) and X-ray photoelectron spectroscopy (XPS). Both alloys exhibited typical active–passive behaviors in the potentiodynamic polarization test and presented similar passive current densities. The HR-TEM results revealed that the anodic passive films formed on the surfaces of the two alloys had similar thicknesses (3–5 nm). However, potentiodynamic polarization measurements showed that the DP-HEA had a higher corrosion current density and lower corrosion potential than did the HEA. XPS revealed that the anodic passive film formed on the DP-HEA contained a lower ratio of Cr2 O3 /Cr(OH)3, which led to poor corrosion resistance properties, as demonstrated by the potentiodynamic polarization measurements and electrochemical impedance spectroscopy.